Advancements in digital drilling technology for deep engineering: a review - Fan, Keqi (Frontiers in Earth Science, 2025)
In deep engineering, the in-situ measurement of engineering rock properties is a key issue in projects such as energy storage and resource mining. Numerous researches devoted to adopting the digital drilling methods for the in-situ application of deep rock engineering. Interdisciplinary technical means were introduced to improve the accuracy and efficiency of in-situ testing methods. In this paper, the existing progress of digital drilling technology was initially reviewed. The establishment of penetration, cutting, and rock-breaking models was discussed based on the mechanical interaction during rock drilling. Improved understanding of machine-rock interaction behavior can be achieved through solving the deep engineering problems such as detecting structural distribution, obtaining rock engineering parameters, improving drilling and rock breaking efficiency, and reducing testing costs. Importantly, the issues of current research were summarized on the digital drilling method to provide a forecast on the development in deep rock engineering. Future digital drilling technology will combine intelligence, automation and big data analysis to achieve efficient, accurate and safe drilling operations. Through digital twin and remote-control technology, the drilling process will be fully monitored and optimized to improve efficiency and reduce risks.